Beyond worship: the three loyal kings and the changes within the Chinese community in Singapore since 1965 - Lek, Hui Xuan (Nanyang Technological University, 2023)
When Singapore gained independence abruptly in the 1965, one of the government’s priority was to create a nation and a common national identity. Several policies were enacted during this period to aid in this goal and some such as the education and land policies had profound impacts on the ethnic communities. These policy changes resulted in the re-configuring of the social organisations of the Chinese. These changes also affected Chinese religious worship patterns which were heavily dependent on the social organisation of the Chinese. Through the Poh Chung Tian Chor Sian Tong temple, this paper studies the impacts of such political changes on Chinese religious worship and the temple’s responses to them. The paper argues that while the impacts of these socio-political changes resulted in challenges which temples had to grapple with, these changes also created a new socio-political environment which were influential in temples’ responses to them, and allowed temples’ continued relevance in their communities.